Yield and quality in ’Caipira’ melon in fertilization function - Sales, Witalo da Silva; Lobo, Jackson Teixeira; Feitosa, José Fabrício Alves; Camara, Felipe Thomaz da; Costa Junior, Juscelino Martins; Santos, Maria Ângela Cruz Macêdo dos (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The aim of this work was to evaluate the effect of different fertilizations and ground cover in the yield and quality of the fruits of irrigated ‘Caipira’ melon fruits (Cucumis melo var. acidulus) in tropical semiarid conditions. The experimental design was a randomized block design in a 3x2 factorial arrangement, with three replications. Three fertilization managements were compared (F1 - only mineral fertilization in the foundation, F2 – mineral and organic fertilization in the foundation, F3 - mineral fertilization in the foundation and leaf fertilization) under bare soil conditions and covered with black mulching. Five useful plants were evaluated per plot. The amount of mineral fertilization recommended for cultivation (40 kg ha-1 of Nitrogen, 120 kg ha-1 of P2O5 and 40 kg ha-1 of K2O) was applied in the plots. The fruit average weight – FAW (kg), yield - Y (t.ha-1), fruit length – FL (cm) and diameter - FD (cm), fruit pulp thickness - FPT (cm), fruit cavity diameter – FCD (cm) and total soluble solids – SS (°Bx) were evaluated. A comparison of the means between fertilization and soil cover was done using the Tukey test with 5% probability. The use of mineral fertilization associated with the organic at the foundation provided superior results for the variables analyzed, except for the SS and FCD. The use of mulching was responsible for increasing the FAW, Y and SS in the melon.